ANALYSIS OF THE CORRELATION OF POPULATION GROWTH TO FULFILLMENT OF THE SUPPORT CAPACITY OF EDUCATIONAL FACILITIES IN SUKABUMI DISTRICT (CASE STUDY OF CISAAT DISTRICT AND SURADE DISTRICT) - Haris Darsono (Universitas Pendidikan Indonesia, 2022)
The development of a city cannot be separated from the availability of city facilities and infrastructure to fulfill people's needs. One very important aspect is the aspect of education, in which the development of these educational facilities is not only the domain of the government in its implementation, recently there have been many private roles that have made breakthroughs in the education sector. This research collects data accumulatively based on the level of education starting from elementary, junior high to high school, without disaggregating education data. The quantitative method used in this research uses data sources from the Statistics Agency of Sukabumi Regency. The data is processed and tested in advance related to the correlation between related variables, the results of the correlation test will show whether there is a significant relationship between the rate of population growth and the number of students and the fulfillment of the carrying capacity of existing schools. If the test results find a significant correlation, it will be followed by a projection of the carrying capacity needs of educational facilities for the next 10 years. It is hoped that the results of this study will become a reference for increasing the capacity and quality of educational facilities in the future. From the research results it was found that there was a significant relationship between population growth and the number of students and the carrying capacity of educational facilities. Based on this research, it is possible to calculate the estimated need for school facilities for the next 10 years which can be used as a basis for planning and developing educational facilities in Sukabumi district.